SOLAR RADIATION USE EFFICIENCY AND GROSS PROTEIN OF SORGHUM FORAGE ARE MODIFIED BY THE CUTTING MANAGEMENT - Schneider, Julia Renata (2019)
The purpose of this study is to determine the growth, the solar radiation use efficiency, and the gross protein of sorghum forage under different cutting management. A unifactorial design in random blocks (cutting management) was used, varying from no-cut treatment to four cuts. The first cut occurred 44 days after sowing, the second one after 23 days of regrowth, the third one after 25 days of regrowth, and the last one after 40 days of regrowth. The efficiency of the sorghum forage’s solar radiation use reduces as the number of cuts increases. The sorghum forage’s gross protein increases with cutting management. Therefore, for a sorghum forage crop, it is recommended to restrain the cutting management up to three times during the crop cycle, since it has the biomass potential production, and the cuts should be made at every 25 days, depending on the increase of dry mass. After that, the cutting management should not be done, mainly due to the low radiation use efficiency, reduced dry mass accumulation, and low material quality.Keywords: forage; grazing; tillering.